How to measure the socioeconomic impact of inclusive sports activities on people with social exclusion: Inclusive Rugby within the framework of the European Union - Ferrandis Martínez, Adrián; García-Cardona, Cristina; Sánchez Cabrera, José Vicente (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
There is a great consensus within academia regarding the need to take into account a large number of variables in order to conceptualize and measure the inclusion or, therefore, the social exclusion experienced by certain groups. Through an in-depth study of the literature, pilot cases and similar projects, a system of indicators has been created with the aim of measuring the socio-economic impact of a socio-sports activity linked to the inclusion of people with functional diversity. The results of this system are applied in the VARIED pilot case, a European project carried out in five countries of the European Union itself.